Post-discharge evaluation of patients with Covid-19 infection - Ayşenur Canan Benli Özçakır; Zeliha Kaya Erten; Hümeyra Aslaner; Mebrure Beyza Gökçek; Adil Çetin (SERNEV, 2022)
Introduction: This study was conducted retrospectively, cross-sectional and descriptively to evaluate the telemonitoring results of discharged patients who had been hospitalized due to Covid-19 during the pandemic.Methods: This study was composed of data which were obtained through the folders of 862 patients who had gotten their Covid-19 Polymerase Chain Reaction (PCR) tests positive, were treated in hospital and discharged between 28.08.2020 and 16.09.2020. This study was completed with folders of 760 patients whose data were overall. Descriptive statistics were given as mean, standard deviation, median, minimum and maximum. Percentages were used for categorical data. Also, the Chi-Square test was used to determine differences between the groups in categorical variables. Kolmogorov-Smirnov test was used so as to analyze normal distribution of data.Results: In the study, the age median of patients who stated their clinical condition as good and average, was lower compared to patients whose clinical status was bad (p=0.001). 45% of patients with poor condition were rehospitalized and 35% of them were directed to emergency service (p lt;0.001).Conclusions: Results have demonstrated that even if those patients were discharged, their problems still continued in their homes, and they need support. Moreover, it is considered that home-monitoring and home attendant care services for elderly patients have to be improved qualitatively.Keywords: Covid-19, Home Care, Discharge Period